From in-patient treatment to clinical day treatment: Patients' experiences and views. (1st June 2013) - Zulehner, Christoph; Them, Christa; Raich, Margit
<x xml:space="preserve">Abstract</x> The objective of this study is to compare the changes found from in-patient treatment to clinical day treatment in the ophthalmic department of an Austrian hospital. The phase of process change was utilized in the structure of field research. Identical patient groups were interviewed, and each participant had had cataract operations on both eyes. They have experienced both forms of treatments. The main conclusion drawn from this study was that the majority of the patients preferred clinical day treatment. The essential indicator of success for a clinical day treatment is a functioning social structure at home that guarantees pre-care, aftercare, and necessary process support. From the organizational perspective, a successful implementation requires appropriate structural adjustments and a strong focus on information and communication systems in order to establish mutual trust between patients and clinical staff.